Prediction of MASLD using different screening indexes in Chinese type 2 diabetes mellitus - Mengmeng Hu; Jingyu Yang; Beibei Gao; Zhoulu Wu; Ying Wu; Dandan Hu; Qiong Shen; Lei Chen (Diabetology & Metabolic Syndrome)
Abstract Background Formerly known as non-alcoholic fatty liver disease (NAFLD), metabolic dysfunction-associated steatotic liver disease (MASLD) has now become the most widespread chronic liver disease worldwide. The primary goal of this study is to assess the ability of different indexes (including VAI, TyG, HOMA-IR, BMI, LAP, WHtR, TyG-BMI, TyG-WC, and TyG-WHtR) to predict MASLD in individuals diagnosed with type 2 diabetes mellitus (T2DM), particularly within the Chinese population. Methods This cross-sectional study involved 1,742 patients with T2DM, recruited from the Metabolic Management Centers (MMC) at Suzhou Municipal Hospital. Abdominal ultrasonography was employed for MASLD diagnosis in patients with T2DM. The predictive accuracy of various screening indexes for MASLD in the Chinese T2DM population was evaluated using logistic regression and receiver operating characteristic (ROC) curve analyses. Results Among the 1,742 participants, 996 were diagnosed with MASLD. After adjusting for potential confounding factors, positive associations with the risk of MASLD were found for all the nine indexes. The lipid accumulation product (LAP) exhibited the greatest predictive value for detecting MASLD, with an area under the curve (AUC) of 0.786(95%CI 0.764,0.807), followed by BMI(AUC = 0.785), VAI(AUC = 0.744), TyG(AUC = 0.720), WHtR(AUC = 0.710) and HOMA-IR(AUC = 0.676). The composite Indexes (TyG-BMI, TyG-WC, TyG-WHtR) also showed considerable predictive ability with AUCs of 0.765, 0.752 and 0.748, respectively. Conclusion Our results indicated that all nine indexes have favorable correlations with the risk of MASLD, and most of them have a good performance in predicting MASLD. According to our study, LAP was a reliable index for predicting MASLD among Chinese T2DM patients. The exploration of non-invasive screenings will provide significant support for the early detection and diagnosis of MASLD.